1999
DOI: 10.1099/00222615-48-1-79
|View full text |Cite
|
Sign up to set email alerts
|

Induction of systemic and mucosal immune response in mice immunised with porins of Salmonella typhi

Abstract: Porins, purified from Salmonella @phi strain 0901 provided 90% protection to BALB/c mice against a lethal dose (300 X LD50) of S. typhi Ty2 when given intraperitoneally. To measure the porin-induced cellular immune responses, macrophages and lymphocytes were isolated from spleen and lamina propria (LP) of porin immunised-challenge mice and of infected and control mice; T-cell phenotypes, lymphocyte proliferation and cytokine production were studied. The secretory IgA (sIgA) antibody level in the intestinal flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…3b); this may be due to a change in the antigen expression on the surface of the antigen-presenting cells along with the major histocompatibility complex (MHC) molecules by that time. It was interesting to observe that a significantly lower amount of IROMPs (1 ìg) was required for the transformation of lymphocytes in this study, in contrast to the porins (20 ìg) used previously (Singh et al, 1999). This points towards the sensitivity of OMPs regulated by iron availability.…”
Section: Lymphocyte Proliferationcontrasting
confidence: 52%
See 2 more Smart Citations
“…3b); this may be due to a change in the antigen expression on the surface of the antigen-presenting cells along with the major histocompatibility complex (MHC) molecules by that time. It was interesting to observe that a significantly lower amount of IROMPs (1 ìg) was required for the transformation of lymphocytes in this study, in contrast to the porins (20 ìg) used previously (Singh et al, 1999). This points towards the sensitivity of OMPs regulated by iron availability.…”
Section: Lymphocyte Proliferationcontrasting
confidence: 52%
“…5 ìg of the protein was observed to enhance the DTH response significantly. This is in contrast to a 50 ìg dose of the same antigen as discussed recently (Chanana et al, 2005) or of porins extracted under normal conditions (Singh et al, 1999). Since organisms under environmental stresses have been reported to express more virulence determinants, lower concentrations of bacteria/ bacterial products might be required.…”
Section: Dth Responsementioning
confidence: 79%
See 1 more Smart Citation
“…Earlier studies have shown that porins of S. typhi induce both cellular and humoral immune response (6,25,33). We, in another study, also observed that porins induce Tcell responses both at systemic and mucosal levels (24). In the present study, the Vi and porin were first purified from S. typhi Ty2 and S. typhi 0901 strains, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…also induces sIgA in the intestine (24). Therefore, porin might be playing an important role in the conjugateinduced sIgA.…”
Section: Discussionmentioning
confidence: 99%